Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) terhadap Hasil Belajar Matematika Siswa Kelas X MAN 1 Sleman - Esta Fania Hariani; Nanang Khuzaini (Mataram University, 2026)
This study aimed to determine the effect of the Contextual Teaching and Learning (CTL) model on the mathematics learning outcomes of tenth-grade students at MAN 1 Sleman and to compare its effectiveness with conventional learning. The study employed a quantitative approach using a quasi-experimental method with a Non-equivalent Control Group Design. The sample consisted of 72 students, divided into an experimental class (36 students) and a control class (36 students), selected through purposive sampling. Data were collected using a validated and reliable essay test on statistics. The data were analyzed using descriptive statistics, normality and homogeneity tests, paired samples t-test, independent samples t-test, and Cohen's d effect size analysis. The results revealed a significant improvement in students' mathematics learning outcomes after the implementation of the CTL model. The independent samples t-test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between the experimental and control groups. In addition, the effect size analysis produced a Cohen's d value of 0.87, which falls into the large category, indicating that the CTL model had a strong practical effect on improving students' mathematics learning outcomes. These findings suggest that the CTL model is an effective alternative learning strategy for promoting meaningful, contextual, and student-centered mathematics learning.